Estimating the reproduction number from the initial phase of the Spanish flu pandemic waves in Geneva, Switzerland - Gerardo Chowell; Catherine E. Ammon; Nicolas W. Hengartner; James M. Hyman (Mathematical Biosciences and Engineering)
At the outset of an influenza pandemic, early estimates of the number of secondarycases generated by a primary influenza case (reproduction number, $R$) and its associateduncertainty can help determine the intensity of interventions necessary for control.Using a compartmental model and hospital notification data of the first two waves of theSpanish flu pandemic in Geneva, Switzerland in 1918, we estimate the reproduction numberfrom the early phase of the pandemic waves. For the spring and fall pandemic waves, weestimate reproduction numbers of $1.57$ ($95%$ CI: $1.45$, $1.70$) and $3.10$ ($2.81$, $3.39$),respectively, from the initial epidemic phase comprising the first $10$ epidemic days of thecorresponding wave. Estimates of the variance of our point estimates of $R$ were computed viaa parametric bootstrap. We compare these estimates with others obtained using differentobservation windows to provide insight into how early into an epidemic the reproductionnumber can be estimated.